„Die Hoffnung, informiert zu sein“. Effekte der Corona-Warn-App - Urban, Monika (Präv Gesundheitsf, 2021)
BACKGROUND: The Corona-Warning-App of the Robert Koch-Institute is the most widely used digital public health intervention during this pandemic. Nevertheless, in October 2020, at the beginning of a new wave of infection, it reaches just one fifth of the population. This means that the app’s potential to provide information about potential infections, which have taken place unnoticed, is dwindling. AIMS: The aim of the study is to explore the subjective perception and impact of the app on the individual, as well as the inhibiting and facilitating factors of its use. These effects can provide conclusions about the needs of the population and accordingly challenges for public health. MATERIALS AND METHODS: The dataset was created through two procedural steps. The first step is a forum analysis of a total of 300 reviews. The second step consists of 40 qualitative, semi-structured interviews. The data were inductively–deductively coded and evaluated along a content-structuring form of qualitative content analysis. RESULTS AND CONCLUSION: The effects of the app are a result of complex interactions. Of central importance for the dynamics are public spaces and social interactions, which are perceived as dangerous during this pandemic. Against this background, practices with the app can generate new visibilities that lead to a reassessment of the concrete threat. This again, can reopen possibilities for action. However, critical positions on data protection and data security may lead to new insecurities and possibly to the rejection of the app.